The Influence of Fatigue on Throwing and YBT-UQ Performance in Male Adolescent Handball Players - Bauer, Julian; Hagen, Marco; Weisz, Nelson; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2020)
Purpose: The goal of the present study was to assess the effects of fatigue on throwing and Upper Quarter Y Balance Test (YBT-UQ) performance in male adolescent handball players. We hypothesized that throwing and YBT-UQ performance will be decreased in response to an upper-body fatigue-protocol. Method: All male participants (N = 24, age: 14.8 ± 0.7 yrs) were handball players of a regional youth selection team. A radar gun was used for the assessment of throwing velocity. The YBT-UQ was executed assessing medial, inferolateral and superolateral reach directions normalized to the upper limb length together with a composite score. Immediately following a fatigue protocol of different sets of push-ups until failure (i.e., not being able to perform 60% of the initial maximal amount of push-ups), throwing and YBT-UQ performance were assessed again. Results: Fatigue resulted in a significant decrease in throwing velocity (−3%, p = 0.022, d = 0.32). Concerning YBT-UQ, the fatigue protocol produced significant decreases for the superolateral reach direction (throwing arm reach: −5%, p = 0.017, d = 0.39; non-throwing arm reach: −10%, p < 0.001, d = 0.87) and the composite score (throwing arm reach: −2%, p = 0.026, d = 0.31; non-throwing arm reach: −4%, p = 0.001, d = 0.52) but not for the medial and the inferolateral reach directions. Conclusions: Fatigue was found to be an impairing factor for throwing performance and shoulder mobility and stability. Therefore, a lower level of fatigue and/or a higher tolerance of fatigue is desirable. Strength-endurance and mobility exercises especially for the shoulder girdle may be a valuable addition for the training routine of youth handball players.